2008
DOI: 10.1007/s11211-008-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Justice and Affect Intensity: Understanding Reactions to Regulatory Authorities

Abstract: Why is it that some people respond in a more negative way to procedural injustice than do others, and why is it that some people go on to defy authority while others in the same situation do not? Personality theorists suggest that the psychological effect of a situation depends on how a person interprets the situation and that such differences in interpretation can vary as a function of individual difference factors. For example, affect intensity-one's predisposition to react more or less emotionally to an eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 46 publications
3
46
0
1
Order By: Relevance
“…Trust in the benevolence and good will of individual officers is central to the legitimacy of policing as an institution of social control (Sunshine & Tyler, 2003;Tyler, 2006;Tyler & Huo, 2002;Tyler & Wakslak, 2004). Procedural justice and police legitimacy involve subjective, psychological judgments (Murphy, 2009b;Piquero et al, 2004;Wolfe, 2011), so it was predicted here that officers' requests for consent to search would be construed by drivers as derogatory or unethical, irrespective of officers' actual reasons for making the stop or the request.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust in the benevolence and good will of individual officers is central to the legitimacy of policing as an institution of social control (Sunshine & Tyler, 2003;Tyler, 2006;Tyler & Huo, 2002;Tyler & Wakslak, 2004). Procedural justice and police legitimacy involve subjective, psychological judgments (Murphy, 2009b;Piquero et al, 2004;Wolfe, 2011), so it was predicted here that officers' requests for consent to search would be construed by drivers as derogatory or unethical, irrespective of officers' actual reasons for making the stop or the request.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been found in past research that process-based considerations outweigh outcome favorability, outcome-based considerations are not inconsequential (Murphy, 2009b;Sunshine & Tyler, 2003). The analyses therefore account for whether or not a motorist was ticketed (0 = no; 1 = yes), arrested (0 = no; 1 = yes), or had force used or threatened against them (0 = no; 1 = yes).…”
Section: Variablesmentioning
confidence: 99%
“…For example, in a study of general views of the police and specific views of experiences with the police, Brandl et al (1994) found that people selectively interpreted their own experiences with the police based on their previous general perceptions. In addition, Murphy (2009) determined that individual differences in people's responses to emotional stimuli (officer behavior here) may influence the effect of procedural justice factors on citizen compliance. As such, procedural justice factors may be less effective in getting people to comply if they are highly emotional individuals.…”
Section: The Theory Of Procedural Justice and Process-based Policingmentioning
confidence: 99%
“…There is empirical evidence of tax compliance being positively influenced by perceived justice, both in terms of distributive (Alm, Jackson, and McKee 1992; Kim 2002; Spicer and Becker 1980; Wenzel 2002) and procedural justice (Braithwaite, Murphy, and Reinhart 2007; Hartner et al. 2008; Murphy 2005, 2009; Murphy and Tyler 2008; Murphy, Tyler, and Curtis 2009; Wenzel 2002). Despite justice considerations being mentioned as important for the acceptance or rejection of tax amnesties (Alm, McKee, and Beck 1990; Andreoni 1991; Hasseldine 1998; Lerman 1986; Sausgruber and Winner 2004; Torgler 2007), to the best knowledge of the authors, so far no studies empirically tested the influence of perceived justice on subsequent tax compliance.…”
Section: Introductionmentioning
confidence: 99%